1992
DOI: 10.1002/1097-0142(19920415)69:8<2011::aid-cncr2820690802>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of oral submucous fibrosis. Relationship to risk factors associated with oral cancer

Abstract: Oral submucous fibrosis (OSF) is a chronic disease of the oral mucosa characterized by inflammation and a progressive fibrosis of the lamina propria and deeper connective tissues. It is a condition predominantly seen among people of Indian origin, and an epidemiologic survey done a decade ago showed no less than 250,000 cases in India, a figure that must have increased sharply. OSF is a condition with a high risk of malignant transformation; to date, no conclusive etiologic agent has been identified, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 82 publications
0
74
0
Order By: Relevance
“…Oral submucous ®brosis (OSMF) is a chronic disease of the oral mucosa which occurs predominantly among people of Indian origin and occasionally among other Asians. Sporadic cases have been reported among non-Asians (Europeans) [68,69]. The prevalence of OSMF in India ranges from 0.2 to 1.2% [70].…”
Section: Precancerous Lesions/conditions and Malignant Transformationmentioning
confidence: 99%
“…Oral submucous ®brosis (OSMF) is a chronic disease of the oral mucosa which occurs predominantly among people of Indian origin and occasionally among other Asians. Sporadic cases have been reported among non-Asians (Europeans) [68,69]. The prevalence of OSMF in India ranges from 0.2 to 1.2% [70].…”
Section: Precancerous Lesions/conditions and Malignant Transformationmentioning
confidence: 99%
“…The risk factors associated with the development of cancer in OSMF needs to be understood. [18] In some cases the submucosal layer can show fibrosis prior to lamina propria involvement in the early stage of OSMF. [2] In such cases the clinical manifestations of xerostomia [19] leading to candidal colonization, [20,21] decay, early muscular involvement leading to reduction in mouth opening, alterations in the epithelium can occur leading to lethal consequences.…”
Section: Resultsmentioning
confidence: 99%
“…9 Pillai et al 10 also concluded in his review that the etiology is unknown but is probably multifactorial. Main contributing factor as thought by Jayanthi et al 11 , is the use of pan which typically consists of areca nut, tobacco and crude lime wrapped in betel leaf. The onset of this condition is insidious, majority of patients with OSMF present with prodromal symptoms such as burning sensation in the mouth when consuming spicy food, appearance of blisters especially in the palate.The hallmark of the disease is submucosal fibrosis that affects most parts of the oral cavity, pharynx and upper third of the oesophagus.…”
Section: Discussionmentioning
confidence: 99%